Enhancing Optoelectronic Properties of Quasi-2D Ruddlesden–Popper Perovskites via Pseudo–Halogen Doping: A First–Principles Study on Cs₂Pb(SCN)₂Br₂ (Communications in Computational Chemistry, 2025)
Two-dimensional (2D) Ruddlesden-Popper (RP) perovskites have been intensively investigated due to their superior stability andoutstanding optoelectronic properties. Although A-site doping in quasi-2D RP-phase perovskites has been extensively studied,the effect of X-site doping remains unknown. Using first-principles calculations, this work demonstrates that ${\rm SCN}^-$ substitutionin ${\rm Cs}_2{\rm Pb(SCN)}_2{\rm Br}_2$ induces a structural transformation from isotropic to anisotropic through octahedral tilting along the $b$-axis,reducing octahedral spacing from 5.17 to 4.88 Å. This structural modification enhances carrier mobility, dramatically increasesexciton binding energy from 30.47 to 145.39 meV, and improves defect tolerance compared to pristine ${\rm Cs}_2{\rm PbBr}_4.$ Thesemodifications synergistically suppress non-radiative recombination pathways while promoting radiative processes, so thatimprove its performance as a promising light-emitting diode (LED) material. These findings establish pseudo-halogensubstitution as a promising strategy for optimizing carrier transport and radiative efficiency in low-dimensional perovskite LEDdevices.
Keywords: Ruddlesden–Popper (RP) perovskites; LED; exciton binding energy; carrier mobility